Kenaikan Jumlah Penduduk Usia Produktif Berkontribusi Positif terhadap Pengangguran di Kabupaten Banyumas - Agus Arifin (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2012)
This research is aimed to study the influence of the number of productive age workforce, economic growth, and the number of small-medium business toward unemployment in Banyumas Regency. This research uses quantitative method by using the secondary data. The analysis methods of this research are Multiple Linier Regression and Elasticity of Coefficient Linier Regression. The result of research shows that each of independent variables, partially, influences the dependent variable (the number of unemployment) in Banyumas Regency. The number of productive age has a positive influence, so that an increasing of the number of productive age workforce will increase the number of unemployment. While, either the economic growth or the number of small-medium business has the negative influence so that each of those variables will decrease the number of unemployment. Keywords: productive age workforce, economic growth, small-medium business, unemployment